ADHD co-morbidities: A review of implication of gene × environment effects with dopamine-related genes. (August 2022) - Kanarik, Margus; Grimm, Oliver; Mota, Nina Roth; Reif, Andreas; Harro, Jaanus
Abstract: ADHD is a major burden in adulthood, where co-morbid conditions such as depression, substance use disorder and obesity often dominate the clinical picture. ADHD has substantial shared heritability with other mental disorders, contributing to comorbidity. However, environmental risk factors exist but their interaction with genetic makeup, especially in relation to comorbid disorders, remains elusive. This review for the first time summarizes present knowledge on gene x environment (GxE) interactions regarding the dopamine system. Hitherto, mainly candidate (GxE) studies were performed, focusing on the genes DRD4, DAT1 and MAOA . Some evidence suggest that the variable number tandem repeats in DRD4 and MAOA may mediate GxE interactions in ADHD generally, and comorbid conditions specifically. Nevertheless, even for these genes, common variants are bound to suggest risk only in the context of gender and specific environments. For other polymorphisms, evidence is contradictory and less convincing. Particularly lacking are longitudinal studies testing the interaction of well-defined environmental factors with polygenic risk scores reflecting the dopamine system in its entirety. Graphical Abstract: ga1 Highlights: Much of health burden by ADHD is owing to co-morbidities. Major co-morbidities include depression, substance use disorder and obesity. Co-morbidities have early origin and genetic and environmental components. Genes shaping the dopamine system impact ADHD and co-morbidities over life course. The whole dopamine gene cluster should be examined in gene × environment analyses.